Carbene-catalyzed dynamic kinetic resolutions and cycloaddition reactions via acylazolium intermediates - Song, Runjiang (Nanyang Technological University, 2022)
This thesis focuses on exploring the reactivity of N-heterocyclic carbene (NHC) catalyst-derived acylazolium intermediates. In particular, the thesis is mainly focused on NHC-catalyzed dynamic kinetic resolution (DKR) and cycloaddition reactions through formation of acylazolium intermediates. It contains three chapters: Chapter 1 provides a brief review on the history and development of NHCs in organic catalysis. A number of classical reactive intermediates and key reaction modes in NHC catalysis are summarized. Literature studies closely related to the thesis work are introduced. Chapter 2 describes an NHC-catalyzed DKR and transesterification reaction for asymmetric synthesis of optically enriched α-aryloxycarboxylic esters with up to 99% yield and 99:1 er value. The facile interconversion between two NHC-activated diastereomeric acylazolium intermediates allows for highly efficient DKR to occur. The products from our strategy can readily undergo further transformations to produce chiral herbicides and other functional molecules. Chapter 3 presents a highly chemo- and enantioselective organocatalytic tandem reaction between hydroxylamines and bromoenals. The reaction provides access to isoxazolidin-5-ones in good yields and satisfactory enantioselectivities. Chapter 4 provides the conclusion and perspective of this thesis, including potential scientific and real-world applications derived from our study.